2012
DOI: 10.1002/per.838
|View full text |Cite
|
Sign up to set email alerts
|

Higher Extraversion and Lower Conscientiousness in Humans Infected with Toxoplasma

Abstract: Toxoplasmosis is associated with specific differences in the personality of infected subjects relative to non-infected subjects. These differences are usually considered to be a side effect of the manipulative activity of the parasite aimed to increase the probability of its transmission from the intermediate host to the definitive host by predation. The personality of infected subjects was studied mostly using the Cattell's questionnaire. However, this questionnaire is now considered outdated and has been mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…About 10 published studies have demonstrated associations of toxoplasmosis with human personality traits mostly using Cattell's 16PF and Cloninger's TCI questionnaires; for review, see [26], [43], [44]. Only one study, showing positive association of toxoplasmosis with extroversion and its negative association with conscientiousness, used the NEO-PI-R questionnaire [45]. A correlation study has also shown that the difference in the prevalence of latent toxoplasmosis between the general populations of particular countries can explain a significant portion of the variance in aggregate neuroticism among populations [46].…”
Section: Discussionmentioning
confidence: 99%
“…About 10 published studies have demonstrated associations of toxoplasmosis with human personality traits mostly using Cattell's 16PF and Cloninger's TCI questionnaires; for review, see [26], [43], [44]. Only one study, showing positive association of toxoplasmosis with extroversion and its negative association with conscientiousness, used the NEO-PI-R questionnaire [45]. A correlation study has also shown that the difference in the prevalence of latent toxoplasmosis between the general populations of particular countries can explain a significant portion of the variance in aggregate neuroticism among populations [46].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries in Europe, South and Central America, and Africa, more than 50% of the population acquire this parasitic infection during their life [9], [10]. Infected subjects who carry the dormant stages of this protozoan parasite for the rest of life differ from the uninfected ones in the personality profile [11], reaction time [12], secondary sex ratio [13], olfactory preferences [14], risk of schizophrenia [15], [16], brain cancer [17], traffic accidents [18], and suicides [19] [20]. The amount of change usually increases with the duration of toxoplasmosis and most changes were also observed in artificially infected laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important obstacle to the study of the causal relationship between Toxoplasma infection and various toxoplasmosis-associated traits. For example, the lower NEO PI-R conscientiousness in infected subjects (Lindová et al, 2012) could be an effect of the infection or it may be that there is a higher probability of infection in persons with lower conscientiousness who may have a lower tendency to adhere to hygienic standards. In some cases, the causality direction is quite obvious.…”
Section: Advantages and Disadvantages Of The Toxoplasma-human Model Fmentioning
confidence: 99%
“…Some studies also suggest that infected subjects have higher scores on Cloninger's ST -self-transcendence Skallová et al, 2005). The NEO-PI-R questionnaire showed more extraversion in infected subjects, both men and women, and less conscientiousness in comparison with Toxoplasma-free subjects (Lindová et al, 2012). On the basis of predictions of the manipulation theory and introspection of the Toxoplasma-infected author, a special questionnaire called Toxo94 was constructed (Flegr, 2010b).…”
Section: Changes In the Personality Profile Of Humans With Latent Toxmentioning
confidence: 99%